A black phosphorus based synergistic antibacterial platform against drug resistant bacteria. Issue 39 (13th September 2018) - Ouyang, Jiang; Liu, Ren-Yu; Chen, Wansong; Liu, Zhenjun; Xu, Qunfang; Zeng, Ke; Deng, Liu; Shen, Liangfang; Liu, You-Nian
Abstract : Black phosphorus nanosheets were decorated with Ag nanoparticles through an in situ growth strategy, exhibiting synergistic antibacterial activity against drug-resistant bacteria. Abstract : In the fight against pathogenic bacteria, traditional antibiotic therapy is challenged by low efficiency and drug resistance. These drawbacks motivate the development of synergistic antibacterial therapy, but there is a lack of efficient synergistic platforms. Herein, with methicillin-resistant Staphylococcus aureus (MRSA) as a pathogenic bacterial model, we explored the potential of black phosphorus (BP) as a synergistic therapeutic platform for drug resistant bacterial infection. Acting as a substrate, reductant and stabilizer, BP nanosheets were decorated with Ag nanoparticles (NP) through an in situ growth strategy. The photothermal effect of the BP nanosheets allows Ag@BP nanohybrids to rapidly disrupt a bacterial membrane under near infrared (NIR) light irradiation. Moreover, the slowly released Ag + elevates oxidative stress and sustainably suppresses bacterial proliferation for a long time. The combination of these two aspects endows the Ag@BP nanohybrids with synergistically enhanced antibacterial performance. Different from traditional antibiotics, the antibacterial effects of the Ag@BP nanohybrids are independent of the bacterial structure, which bypasses the issue of drug resistance. The in vivo studies show that the Ag@BP nanohybrids efficiently decrease the MRSA bacterial burden in mice and minimize infection associated tissue lesions. Besides, the excellent biocompatibility of the Ag@BP nanohybrids guarantees their biosafety for future clinical applications. Accordingly, this work demonstrates the potential of the BP nanosheets in the synergistic antibacterial therapy against drug resistant bacteria, and paves the way for developing 2D semiconductor based synergistic antibacterial nanodrugs.